TOWARDS HERITAGE TRANSFER IN SOCOVOS (ALBACETE): FIRST ARCHAEOLOGICAL WORKS (Salduie, 2025)
This article presents the results of the first phase of ar-chaeological intervention in Socovos (Albacete), car-ried out within the framework of the Almenara Project. The work focused on three key sites: Solana del Molin-ico, Peña Bermeja, and the Castle of Socovos. Through documentation, conservation, and material analysis, a foundation has been laid for the preservation and enhancement of local heritage. The installation of a protective enclosure at the rock art site, the planimetric documentation of the early medieval settlement, and the creation of a heritage classroom reflect a clear orientation toward community participation and the social activation of heritage.
Keywords: Archaeological heritage; Social archaeology; Archaeological survey; Heritage conservation